The Arab-Israeli conflict : an introduction and documentary reader - Mahler, Gregory S., 1950-; Mahler, Alden R. W. (London ; New York : Routledge, 2010)
Focuses on the foreign policy of the Arab-Israeli peace process and the progress made. Examining seventy key documents related to the conflict and placing them in their historical context, this book presents an overview of the situation, looking at both Israeli and Palestinian perspectives.
Part I: Introductory chapter. Part II: From Herzl (1896) to Recognition as a State (1949) 1. Theodor Herzl, The Jewish State (1896) 2. The Basle Program, Resolutions of the First Zionist Congress (August 30, 1897) 3. Sir Henry McMahon: The McMahon Letter (October 24, 1915) 4. The Sykes-Picot Agreement (1916) 5. The Balfour Declaration (November 2, 1917) 6. The Weizmann-Feisal Agreement (January 3, 1919) 7. The White Paper of 1922 (June, 1922) (the "Churchill White Paper") 8. The Mandate for Palestine (July 24, 1922) 9. British Prime Minister Ramsay MacDonald letter to Chaim Weizmann (February 13, 1931) 10. The Palestine Royal Commission (Peel Commission): Report (July 24, 1937) 11. British Government: Policy Statement Against Partition (November 11, 1938) 12. British Government: The White Paper (May 17, 1939) 13. Zionist Reaction to the White Paper (1939) 14. The Biltmore Program: Towards a Jewish State, May 11, 1942 15. United Nations Resolution 181, The Partition of Palestine ( November 29, 1947) 16. Declaration of the Establishment of the State of Israel (May 14, 1948) 69 17. Creation of a Conciliation Commission, General Assembly Resolution 194 December 11 1948) 18. Admission of Israel to the United Nations, General Assembly Resolution 273 (11 May 1949) Part III: From Recognition (1949) Through the Start of a Peace Process (1978) 19. General Assembly Resolution 303: Palestine: Question of an international regime for the Jerusalem area and the protection of the Holy Places (December, 1949) 20. State of Israel : Law of Return, July, 1950 (5710) 21. U.N. Security Council: Resolution 95, Concerning... the Passage of Ships Through the Suez Canal (Sept. 1, 1951) 22. Palestine National Authority: Palestine Liberation Organization Draft Constitution (December, 1963) 23. Israeli Foreign Minister Abba Eban : Speech to the Security Council of the United Nations (June 6, 1967) 24. Protection of Holy Places Law (June 27, 1967) 25. The Khartoum Resolutions (September 1, 1967) 26. Resolution 242, UN Security Council (November 22, 1967) 27. The Palestinian National Charter: Resolutions of the Palestine National Council (July 1-17, 1968) 28. The Seven Points of Fatah (January 1969) 29. Resolution 338, UN Security Council (22 October 1973) 30. Palestine National Council: Resolutions at the 12th session of the Palestine National Council (June, 1974) 102 31. Interim Agreement between Israel and Egypt (September 4, 1975) 32. Statement to the Knesset by Prime Minister Menahem Begin (November 20, 1977) 33. Statement to the Knesset by President Sadat (20 November 1977) 34. Six-Point Program of the Palestine Liberation Organization (December 4, 1977) 35. The Camp David Accords (September 17, 1978) 36. Peace Treaty Between Israel and Egypt (March 26, 1979) Part IV: From a Peace Treaty (1979) to the Nobel Peace Prize (1994) 37. Basic Law: Jerusalem, Capital of Israel (July, 1980) 38. Saudi Crown Prince Fahd ibn Abd al-Aziaz: The Fahd Plan (August 7, 1981) 39. Golan Heights Law (December 14, 1981) 40. Prime Minister Begin: The Wars of No Alternative and Operation Peace for the Galilee (August 8, 1982) 41. Agreement between Israel and Lebanon (17 May 1983) 42. Palestine National Council: Declaration of Independence (November 15, 1988) 43. Israel's Peace Initiative (May 14, 1989) 44. U. S. Secretary of State James Baker's Five Point Plan (December 6, 1989) 45. Letter of Invitation to the Madrid Peace Conference (October 30, 1991) 46. Israel-PLO Recognition: Exchange of Letters Between Prime Minister Rabin and Chairman Arafat (September 9, 1993) 47. Declaration of Principles on Interim Self-Government Arrangements ["Oslo Agreement"] (September 13, 1993) 48. Israel-Jordan Common Agenda (September 14, 1993) 49. Agreement on the Gaza Strip and the Jericho Area (May 4, 1994) 50. The Washington Declaration (July 25, 1994) 51. Treaty of Peace Between The Hashemite Kingdom of Jordan and the State of Israel (October 26, 1994) 52. Nobel Lecture by Yasser Arafat (December 10, 1994) 53. Nobel Lecture by Shimon Peres (December 10, 1994) 54. Nobel Lecture by Yitzhak Rabin (December 10, 1994) Part V: From Interim Agreements (1995) to the Present Time 55. Israeli-Palestinian Interim Agreement on the West Bank and the Gaza Strip (September 28, 1995) 56. Speech by Yitzhak Rabin to the Knesset Supporting the Israeli-Palestinian Interim Agreement (October 5, 1995) 57. Speech by Prime Minister Rabin at a peace rally (November 4, 1995) 58. Israel-Lebanon Ceasefire Understanding (April 26, 1996) 59. The Wye River Memorandum (October 23, 1998) 60. Address in the Knesset by Prime Minister Elect Ehud Barak presenting his government (July 7, 1999) 61. Sharm el-Sheikh Memorandum and the Resumption of Permanent Status Negotiations (September 4, 1999) 62. Protocol Concerning Safe Passage between the West Bank and the Gaza Strip (October 5, 1999) 63. Trilateral Statement on the Middle East Peace Summit at Camp David (July 25, 2000) 64. Sharm El-Sheikh Fact-Finding Committee Final Report (April 30, 2001) 65. Roadmap to Solution of Israeli-Palestinian Conflict (April 30, 2003) 66. The Disengagement Plan from Gaza Strip and Northern Samaria (April 18, 2004) 67. Prime Minister Ariel Sharon's Address to the Knesset - The Vote on the Disengagement Plan (October 25, 2004) 68. United Nations Security Council Resolution 1701 (August 11, 2006) 69. Announcement of Annapolis Conference (November 20, 2007) 70. Joint Understanding on Negotiations (November 27, 2007)
Includes bibliographical references (p. 292-297) and index.
Keywords: Arab-Israeli conflict; Arab-Israeli conflict -- Sources; Middle East -- Politics and government -- 1945-; Middle East -- Politics and government -- 1945- -- Sources